The role of dietary non-heme iron load and peripheral nerve inflammation in the development of peripheral neuropathy (PN) in obese non-diabetic leptin-deficient ob/ob mice. (3rd April 2019) - Kosacka, Joanna; Woidt, Katrin; Toyka, Klaus V.; Paeschke, Sabine; Klöting, Nora; Bechmann, Ingo; Blüher, Matthias; Thiery, Joachim; Ossmann, Susann; Baum, Petra; Nowicki, Marcin
ABSTRACT: Introduction : Here, we investigated inflammatory signs of peripheral nerves in leptin-deficient obese ob/ob mice and the modulating effects of the exogenous iron load. Methods : Ob/ob and ob/+ control mice were fed with high, standard, or low iron diet for four months. Results : We found intraepidermal nerve fiber degeneration in foot skin and low-grade neuropathic abnormalities including mildly slowed motor and compound sensory nerve conduction velocities and low-grade macrophage and T-cell infiltration without overt neuropathology in sciatic nerves of all ob/ob mice. Low dietary iron load caused more pronounced abnormalities than high iron load in ob/ob mice. Discussion : Our data suggest that dietary non-heme iron deficiency may be a modulating factor in the pathogenesis of peripheral neuropathy in obese ob/ob mice with metabolic syndrome. Once the mechanisms can be further elucidated, how low dietary iron augments peripheral nerve degeneration and dysfunction via pro-inflammatory pathways and new therapeutic strategies could be developed. Abbreviations : CMAP: compound muscle action potential; cSNCV: compound sensory nerve conduction velocity; IENFD: intraepidermal nerve fiber density; LDL: low-density lipoprotein; MetS: metabolic syndrome; MNCV: motor conduction velocity; NCV: nerve conduction velocity; PN: peripheral neuropathy; PNS: peripheral nervous system; STZ: streptozotocin; T2D: type 2 diabetes mellitus; TNF alpha: tumor necrosis factor alpha; WHO: World Health Organization